Rural tourism and its sustainability in Kashmir: A study of district Shopian - Danish Iqbal Raina; Sajad Ahmad Bhat; Ajaz Dar; Khushboo Bilal; Parvez Abdulla (Journal of Rural Tourism, 2025)
Purpose - The purpose of the current study is to examine the sustainability of rural tourism in Kashmir, specifically focusing on District Shopian. It explores the local residents' perceptions and reactions to the impacts of tourism, particularly in relation to challenges that hinder the development of sustainable rural tourism.Methodology/Design/Approach - The research delves into qualitative analysis, gathering insights from local residents regarding the impacts of tourism. It assesses their concerns about the exploitation of local resources and examines the participation (or lack thereof) of local communities in government-led rural tourism initiatives. The study also evaluates the effectiveness of these initiatives and policies.Finding - The findings indicate that local residents are concerned about the negative impacts of tourism, particularly the exploitation of natural and cultural resources. They feel that the benefits of tourism are minimal, and the government’s rural tourism initiatives have not contributed significantly to the improvement of the village economy. There is a clear dissatisfaction with the limited participation of locals in tourism-related decision-making processes. Originality/Value - The study offers new insights into the dynamics of rural tourism in Kashmir, particularly focusing on the alignment of tourism policies with the needs of local communities and the goals of sustainable development. It calls for significant reforms in the approach to rural tourism, emphasizing the need for genuine community involvement to ensure long-term sustainability and equity.